Barriers to the Early Cochlear Implantation of Deaf Children - Lester, Elizabeth B. (2011)
OBJECTIVE: Identify social and healthcare system factors which prevent congenitally deaf children from receiving cochlear implants in a timely fashion. STUDY DESIGN: Retrospective chart review and parental interviews. SETTING: University medical center hospital in a state with mandatory newborn hearing screening (NBHS). PATIENTS: 59 congenitally deaf children who received cochlear implant(s) between 1/1/2002 and 5/1/2009. INTERVENTIONS: Demographic and healthcare details were collected from the 59 patients. MAIN OUTCOME MEASURE: Age at implantation. RESULTS: Thirty-four patients received implants at or before age 2 years (average age at implant surgery = 14 months) and 25 patients received implants after age 2 (average age = 65 months). The presence of NBHS (p<0.001) and type of health insurance (p=0.05) the child had at the time of CI surgery were significant predictors of age at implantation. The following factors were associated with increased risk of delayed implantation: no NBHS (RR=2.63), NBHS not identifying hearing loss (RR=1.63), Medicaid insurance alone (RR=1.21) or in combination with private insurance (RR=1.79), family physician as primary care provider (RR=1.50), audiologist (RR=1.30) or otolaryngologist (RR=1.31) as secondary care providers (vs. implant center RR=0.23). The main reasons for delay in CI surgery after age 2 were also identified and include slow referrals for care (n=8) and parental delays (n=5). CONCLUSIONS: The data suggest placing special focus on children with associated risk factors, ensuring newborn hearing screening, and parent and primary care provider education on the importance of early intervention and referral to an implant center would likely limit delays in children receiving CIs.